2024
DOI: 10.1002/glia.24517
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal small extracellular vesicles carrying miR‐181c‐5p contribute to the pathogenesis of epilepsy by regulating the protein kinase C‐δ/glutamate transporter‐1 axis in astrocytes

Limin Ma,
Qingyuan Wu,
Yu You
et al.

Abstract: Information exchange between neurons and astrocytes mediated by extracellular vesicles (EVs) is known to play a key role in the pathogenesis of central nervous system diseases. A key driver of epilepsy is the dysregulation of intersynaptic excitatory neurotransmitters mediated by astrocytes. Thus, we investigated the potential association between neuronal EV microRNAs (miRNAs) and astrocyte glutamate uptake ability in epilepsy. Here, we showed that astrocytes were able to engulf epileptogenic neuronal EVs, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In the pathological setting, many EVs are playing the role of villains, exacerbating the hostile environment of the disease. For example, in a mouse model of TBI, EVs are significantly increased in the peripheral blood, and highly express pro-coagulant TFs on their surface and carry various inflammatory mediators, such as inflammatory vesicles, to amplify the inflammatory response, leading to lung epithelial cell death and blood-gas barrier disruption, and even affecting coagulation [ 70 ], In addition, brain-derived EVs activate leukocytes and platelets in the induction of systemic coagulation disorders after TBI and inflammation [ 71 , 72 ]; in epileptic mechanisms, it was found that epileptogenic neuron-derived EVs carrying miR-181c-5p reduced glutamate uptake capacity of astrocytes and promoted susceptibility to epilepsy [ 73 ]. Therefore, before selecting EVs as drug carriers, the source of EVs and the physiological and pathological environment of the animal model must be considered; EVs from different sources have different biological functions and targeting sites, which will affect the efficiency of drug delivery.…”
Section: Extracellular Vesicles(evs)mentioning
confidence: 99%
“…In the pathological setting, many EVs are playing the role of villains, exacerbating the hostile environment of the disease. For example, in a mouse model of TBI, EVs are significantly increased in the peripheral blood, and highly express pro-coagulant TFs on their surface and carry various inflammatory mediators, such as inflammatory vesicles, to amplify the inflammatory response, leading to lung epithelial cell death and blood-gas barrier disruption, and even affecting coagulation [ 70 ], In addition, brain-derived EVs activate leukocytes and platelets in the induction of systemic coagulation disorders after TBI and inflammation [ 71 , 72 ]; in epileptic mechanisms, it was found that epileptogenic neuron-derived EVs carrying miR-181c-5p reduced glutamate uptake capacity of astrocytes and promoted susceptibility to epilepsy [ 73 ]. Therefore, before selecting EVs as drug carriers, the source of EVs and the physiological and pathological environment of the animal model must be considered; EVs from different sources have different biological functions and targeting sites, which will affect the efficiency of drug delivery.…”
Section: Extracellular Vesicles(evs)mentioning
confidence: 99%